Methodical Toolkit for Analytical Evaluation of Performance (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article examines the methods of evaluating the effectiveness of the tools of providing flexible management. Examples of using traditional methods of analyzing financial status, financial results and the latest tools for managing the behavior of participants in economic relations, by which one can evaluate performance, and improve the efficiency and quality of managerial decisions to improve performance.The absence of an integral indicator, based on which would be a generalized assessment of the economic performance, necessitates the formation of a coherent system of indicators, and the search for new approaches to the implementation of effective economic diagnosis in order to increase the effectiveness of the functioning of enterprises.
Keywords: Effectiveness, methods, evaluation, analysis, financial sustainability, controlling; @economics